Tailoring cathode composite boosts the performance of proton-conducting SOFCs fabricated by a one-step co-firing method. Issue 7 (July 2018) - Dai, Hailu; Da'as, Eman Husni; Shafi, Shahid P.; Wang, Huiqiang; Bi, Lei
Abstract: A strategy of tailoring the ceramic cathode composite is presented to improve the performance of proton-conducting solid oxide fuel cells (SOFCs) prepared by a one-step co-firing process. Comparing to the conventional way of using BaCe0.7 Zr0.1 Y0.2 O3- δ (BCZY) in the composite cathode for BCZY-electrolyte based cells, the replacement of BCZY by BaZr0.8 Y0.2 O3- δ (BZY) mitigates the reaction between the two ceramic phases in the composite cathode during the co-firing process and also keeps the cathode with sufficient porosity for ample gas diffusion which could assist in adequate cathode reactions. As a result, the BCZY-electrolyte based cell with Sm0.5 Sr0.5 CoO3- δ (SSC)-BZY composite cathode shows a power output of 300 mW cm −2 at 600 °C, which is the largest ever reported for proton-conducting SOFCs prepared by a one-step co-firing process. The strategy of tailoring the composite cathode offers both small ohmic resistance and polarization resistance, providing a promising way to develop single-step co-fired proton-conducting SOFCs.